2002
DOI: 10.1099/00221287-148-11-3431
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the interplay between peripheral reactions encoded by xyl genes and the chlorocatechol pathway encoded by tfd genes for the degradation of chlorobenzoates by Ralstonia eutropha JMP134

Abstract: Many bacteria can grow on chloroaromatic pollutants because they can transform them into chlorocatechols, which are further degraded by enzymes of a specialized ortho-cleavage pathway. Ralstonia eutropha JMP134 is able to grow on 3-chlorobenzoate by using two pJP4-encoded, ortho-cleavage chlorocatechol degradation gene clusters (tfdC I D I E I F I and tfdD II C II E II F II ). Very little is known about the acquisition of new catabolic genes encoding enzymes that lead to the formation of chlorocatechols in R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
12
2
Order By: Relevance
“…Introduction of multiple copies of the tfdC I D I E I F I or tfdD II C II E II F II genes into strain JMP222, a derivative of strain JMP134 lacking pJP4 and therefore unable to grow in 3-CB, allows the derivatives to grow in this compound (27). However, we observed that derivatives of strain JMP222 harboring single chromosomal copies of each tfd gene module or one copy of the tfdC I D I E I F I module and one copy of the tfdD II C II E II F II module did not grow in 3-CB (23). A tfd gene dosage effect has been shown to be important for efficient growth in 3-CB of strain JMP134 derivatives harboring a rearranged form of the pJP4 plasmid (5).…”
contrasting
confidence: 38%
See 4 more Smart Citations
“…Introduction of multiple copies of the tfdC I D I E I F I or tfdD II C II E II F II genes into strain JMP222, a derivative of strain JMP134 lacking pJP4 and therefore unable to grow in 3-CB, allows the derivatives to grow in this compound (27). However, we observed that derivatives of strain JMP222 harboring single chromosomal copies of each tfd gene module or one copy of the tfdC I D I E I F I module and one copy of the tfdD II C II E II F II module did not grow in 3-CB (23). A tfd gene dosage effect has been shown to be important for efficient growth in 3-CB of strain JMP134 derivatives harboring a rearranged form of the pJP4 plasmid (5).…”
contrasting
confidence: 38%
“…This enzyme system efficiently catalyzes the conversion of 3-CB to 3-CC and 4-CC (33). By using pSPM100, a pUT derivative containing the xylSxylXYZL genes, several R. eutropha transconjugants containing chromosomal insertions of the xyl gene cluster were obtained (23). One of the derivatives, strain JMP134::X(pJP4), exhibited significantly less growth in 3-CB than the wild-type strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations